FUNCTIONAL OUTCOME OF ARTHROSCOPE ASSISTED RECONSTRUCTION OF ANTERIOR CRUCIATE LIGAMENT USING BONE-PATELLAR TENDON-BONE GRAFT - Syed Faraz Anwar; Ahmed Mushtaq Khan; Anas Bin Saif; Syed Shehreyar Faraz (Pakistan Armed Forces Medical Journal, 2019)
Objective: To evaluate arthroscopic assisted Anterior Cruciate Ligament (ACL) reconstruction using Bone-Patellar Tendon-Bone (BPTB) graft using anteromedial approach to drill the femoral tunnel followed by accelerated ACL rehabilitation protocol in terms of Lysholm score.